INTEGRATION OF WORLDSKILLS STANDARDS IN VOCATIONAL EDUCATION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
This paper examines the integration of WorldSkills standards into national vocational education and training (VET) systems as a mechanism for improving the quality, relevance, and global competitiveness of technical education. Drawing on case studies, curriculum analysis, and stakeholder interviews, the study highlights the potential of WorldSkills standards to modernize pedagogical practices, promote labor market alignment, and enhance student employability. The paper proposes a framework for the systemic adoption of WorldSkills standards in VET institutions and identifies challenges and enabling factors for successful implementation.